Człowiek bez właściwości czy człowiek o właściwościach uniwersalnych? Antropologiczne paradoksy utopii totalitarnych - Męczkowska-Christiansen, Astrid (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2022)
The subject of the analyses presented here in is the anthropological utopias of totalitarianism: Nazism and communism, with particular attention paid to the modes of conceptualising the human being that are present within them. In the latter area, I notice a clear tension between the articulations of the sublimity of the human being, inscribed in the universalist discourse of subjectivity developed on the basis of the philosophical Enlightenment, and the denigration of the ‘empirical human’, which was accompanied by systemically organised practices of totalitarian regimes, leading to alienation of human beings from specifically human properties. In particularly, I am interested in the nature of identity politics implemented under totalitarian regimes. As part of this research, I identify the mechanisms that hinder the development of personal identities and, at the same time, shape individuals manque: susceptible to the influence of power and committed to the political interests of totalitarian regimes. These mechanisms include: deprivation of needs and the induction of a sense of inferiority; the internalisation of the idea of the chosen people and the induction of an appeal mechanism; the dumbing down of people and indoctrination as a substitute for education; the severing of social bonds; the spread of total care as a function of paternalistic power; the promotion of virtues as a metonymy of education; gender identity politics; deindividuation and the erosion of the faculty of judgement.
Keywords: subjectivity; identity; ideology; Nazism; Communism; identity politics; violence; childhood; upbringing; education; deindividuation; cultivation of virtue